FORMULASI DAN EFEK SALEP EKSTRAK ETANOL DAUN JAMBU BIJI (Psidium guajava,L.) DENGAN BASIS HIDROKARBON TERHADAP LUKA SAYAT PADA TIKUS JANTAN GALUR WISTAR - Ririn Lispita Wulandari; Elya Zulfa; Dwara Andriani Astuti (Universitas Wahid Hasyim Semarang, 2019)
ABSTRACT The ethanol extract of guava leaves (EEGL) is proven to heal various types of wounds.This study aims to determine the physicochemical characteristics of the EEGL ointment with a hydrocarbon base formula and examine the effect of the ointment against cut wounds on wistar male rat. The EEGL was obtained by maceration using 70% ethanol solvent. The ointment made 3 formulas with a ratio of hydrocarbon base composition (cera alba:vaselin album) namely F1 (2.5:92.5)%; F2 (5:90)%; F3 (7.5:87.5)%. The physicochemical characteristics of all ointments examined included organoleptic, homogeneity, pH, viscosity, spreadability, and adhesion. Organoleptic, homogeneity and pH data were analyzed descriptively, while viscosity, spreadability and adhesion data were analyzedstatistically. Testing the effect of all ointment formulas on the wound was done by applying 0.5 gram 2x a day for 9 days compared to wound control without treatment and positive control used commercial product.The parameter of effect measured was the length of the cut wound on the 9th day, then analyzed with the Kruskall Wallis test followed by the Mann Whitney test.The physicochemical characteristics of EEGL ointment (F1, F2, F3) are known that all ointment formulas are brown in color, typical of guava, homogeneous, pH according to skin pH, viscosity and adhesion are significantly different, while the spredability is not significant.The EEGL ointment had an effect on the cut wound of the male wistar rats, ie the length of the wound on the 9th day was reduced and compared to wound controlwas differentsignificantly. Keywords :Guava leaves, ointment, cut of wound.